Permanent Sovereignty vs. International Obligations - Simbolon, Putu George Matthew; Yusro, Mochammad Abizar; Taniady, Vicko (Lentera Hukum, 2024)
This research analyses Indonesia's policies related to downstreaming and restrictions on raw nickel exports that have caused international debate, especially the European Union which complained against Indonesia to the World Trade Organization (WTO) in Dispute Settlement 592 (DS-592). The study explores Indonesia's position as a WTO member that is being questioned for its policy of banning nickel ore exports to the European Union, and examines the DS-592 ruling in relation to the permanent sovereignty debate. This article uses a normative juridical method with doctrinal, comparative, and case approaches. The results show that Indonesia has permanent sovereignty over its nickel ore guaranteed by UN Resolution 1803. Therefore, Indonesia must exercise this sovereignty with due regard to international obligations. Indonesia should learn from China's export regulations as it prioritises export restriction policies rather than export bans. By applying China's approach, Indonesia can prevent the problems that occurred in DS 592. However, a series of nickel downstream policies implemented by Indonesia have violated the provisions of the WTO Agreement. This article also explains that the vacuum of the Appellate Body does not negate the EU's authority to retaliate against Indonesia. This article concludes that Indonesia must implement a policy determining the percentage of downstream nickel ore, as well as nickel ore that will be exported. This conclusion has resulted in the theoretical idea that no sovereignty can be exercised in violation of the country's international obligations. Thus, each country must be able to establish policies that can balance national interests with international obligations. KEYWORDS: Export Restrictions, International Obligations, Nickel Ore, Soverignty, WTO.